PENERAPAN PEMBELAJARAN OPEN-ENDED PADA OPERASI DASAR BILANGAN BULAT DI KELAS VII SMP NEGERI 3 PONTIANAK - Rohmah Pila Khoriyani; Edy Yusmin; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to know and describe student’s learning outcome and student’s learning activities in the implementation of open ended learning on integer basic operations at grade VII SMP Negeri 3 Pontianak. The research method was experiment method with a one shot case study design. Based on the data analysis that review two aspects; (1) student’s learning outcomes, there was most students mastering the basic operations of integer, with division is the most controlled integer basic operations and then followed by addition, substraction, and multiplication; (2) student’s learning activities categorized  as high, with listening activity is the highest activity that classified as very high, then followed by visual activities that classified as high, oral activity that classified as enough, and mental activity that classified as enough. Therefore concluded in general that learning using an open ended had positive effect on integer basic operations at grade VII of SMP Negeri 3 Pontianak. Keywords: Open ended, Integer Basic Operations